AS A RESULT OF THE STIPULATION LAW ON LAND IS DESTROYED AS AN OBJECT OF DEVELOPMENT FOR THE PUBLIC INTEREST - Widyarini Indriasti Wardani; Sigit Irianto (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2022)
Land as a source of human life, has economic value, apart from being a means of fulfilling housing as well as a source of life. Legal certainty for owners of land rights has been regulated for sure, but land can be lost or destroyed through natural factors and government regulations. The provisions for destroyed land have been regulated in PP 18 of 2021 and Ministerial Regulation of ATR/BPN NO 17/2021. The determination of destroyed land needs to be more careful, especially concerning the procurement of land rights for the public interest, if it conflicts with the rights of the community as a source of livelihood.